Rapid Stripping of Brass-plating on Fine Saw Wire by Triangle-type Multiple Magnetron Plasmas - Fujiyama, H.; Miyazaki, K.; Matsuo, N.; Kobayashi, Y.; Shinohara, M.; Nishiyama, S. (International Conference on Plasma Surface Engineering, 2013)
To remove brass plating on fine saw wire, line-shaped magnetron plasma source has been newly developed. New type of multiple plasma sources has been developed by applying to multiple-triangle-type electrodes. The stripping effects were successfully established by using high density magnetron source with 20mm gap in an axially applied magnetic field. From the EDS analysis results of wire surface after plasma stripping during 30sec, it is clearly shown that Zn was removed after 10sec stripping and Cu after 30sec. (Fe:38.5%?97.7%, Cu:39.3%?2.43%, Zn:22.2%? 0.03%)